Pastoral Role in Addressing Teenage Pregnancy among High School Girls in Tigania Central Sub-County, Meru County, Kenya - Itonga, Silas Murithi; Kaaria, Zipporah; Mwenda, Jotham M. (International Journal of Professional Practice, 2024)
Teenage pregnancy is one of challenges faced by society today. Consequently, there was a need to establish the utilization of pastoral programs by the church leadership in addressing teenage pregnancy. This study investigated the pastoral role of Church leadership in addressing teenage pregnancy in Tigania Central Sub-County, Meru County. The study used descriptive survey design, and was guided by Social Learning Theory. From a population of 258 Church leaders, 77 selected using random sampling technique, while 50 teenage high school girls were purposively sampled from a population of 500. Data from the Church leaders was collected using structured questionnaires, and Focus Group Discussions was used to collect data from the teenage high school girls. The quantitative data was analyzed using descriptive statistics like percentages, means, and standard deviations, while the qualitative data was analyzed thematically. Results showed that attitudes towards marital sex (92.4%), cultural values and norms on sexual behavior (81.4%) and perspectives towards contraception utilization (82%) were the causes of high prevalence of teenage pregnancy. The study concluded that pastoral programs by the Church leadership were key in addressing teenage pregnancy among high school girls in Tigania West Sub-County, Kenya. The recommends the Church leadership to appoint youth/teenagers patrons in the Churches, place chaplains in Church-sponsored schools, and include teenagers while drawing pastoral programs.